Exploring the Social Structure of a Health-Related Online Community for Tobacco Cessation: A Two-Mode Network Approach - Manas, Shruthi (Stud Health Technol Inform, 2019)
Unhealthy behaviors, such as tobacco use, increase individual health risk while also creating a global economic burden on the healthcare system. Social ties have been seen as an important, yet complex factor, to sustain abstinence from these modifiable risk behaviors. However, the underlying social mechanisms are still opaque and poorly understood. Digital health communities provide opportunities to understand social dependencies of behavior change because peer interactions in these platforms are digitized. In this paper, we present a novel approach that integrates theories of behavior change and Exponential Random Graph Models (ERGMs) to understand structural dependencies between users of an online community and the behavior change techniques that are manifested in their communication using an affiliation network. Results indicate population specific traits in terms of individuals’ engagement in peer communication embed behavior change techniques in online social settings. Implications for personalized health promotion technologies are discussed.